Synchrotron radiation imaging is a powerful tool to image brain microvasculature. Issue 3 (24th February 2014) - Zhang, Mengqi; Peng, Guanyun; Sun, Danni; Xie, Yuanyuan; Xia, Jian; Long, Hongyu; Hu, Kai; Xiao, Bo
Abstract : Synchrotron radiation (SR) imaging is a powerful experimental tool for micrometer‐scale imaging of microcirculation in vivo . This review discusses recent methodological advances and findings from morphological investigations of cerebral vascular networks during several neurovascular pathologies. In particular, it describes recent developments in SR microangiography for real‐time assessment of the brain microvasculature under various pathological conditions in small animal models. It also covers studies that employed SR‐based phase‐contrast imaging to acquire 3D brain images and provide detailed maps of brain vasculature. In addition, a brief introduction of SR technology and current limitations of SR sources are described in this review. In the near future, SR imaging could transform into a common and informative imaging modality to resolve subtle details of cerebrovascular function.